Evaluasi Kekuatan Geometri Jaring Pemantau Deformasi Horizontal Candi Borobudur - Lestari, Dwi; Widjajanti, Nurrohmat (2013)
Previous studies on nonitoring Borobudur’s horizontal deformation have shown that the traverse precisions have not met the requirement standar for deformation analysis. This can be caused by inaccurate measurements of the angles or distance of closed traverse and the minimum redundancy number in adjustment computation. This study aims to analyze the strength of figure of horizontal deformation monitoring network from previous study and evaluate new design of monitoring netwoks which are measured using Total Station. The research is done firstly by evaluating the strength of figure of horizontal deformation network as observed in 2011. Based on this evaluation, new observations of three different network design using Nikon DTM 352 Total Station has been done. Data from the measurement are then processed using the least square adjustment method using minimal constraints. Global test conducted to evaluate the result of the adjustment computation. Further evaluation of the strength of figure is made based on the correlation value between the estimated parameters and the point positions precision is evaluated using their standard deviation values. The results showed that the design of a closed traverse in this study (design-A) has a weak geometry, which isindicated by the correlation values between the parameter are close to -1 or +1. The addition of tie points and the number of redundancies increase the strength of the network significantly, while the measurement precisions contribute significantly to the precision of the estimated parameters.